Pengaruh Promosi Produk, Kualitas Pelayanan Dan Harga Terhadap Keputusan Pembelian Kebab Arfa (Studi Kasus Mahasiswa Universistas Islam Malang) - Sholeh, M Badrus; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine and analyze the simultaneous and partial influence of product promotion, service quality, and price on purchasing decisions of Kebab Arfa. The type of research conducted uses a quantitative approach. The population in this study were consumers of Kebab Arfa, especially UNISMA students who had purchased Kebab Arfa products at least 1 time, the number of which is not known for sure. The sample was determined using the Malhotra formula 18 x 5 = 90 respondents. The results of the study showed that product promotion, service quality, and price simultaneously had a significant effect on purchasing decisions. Product promotion had a negative and insignificant effect on purchasing decisions. Service quality had a significant effect on purchasing decisions. Price had a significant effect on purchasing decisions. Keywords: Product Promotion, Service Quality, Price And Purchasing Decisions